The trauma of colonization: A psycho-historical analysis of one aboriginal community in the North American “North-West” - Robertson, Lloyd Hawkeye (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2016)
Abstract This article examines two models of mass trauma as applied to the social conditions and history of an aboriginal community in the boreal forest of northern Canada. A psycho-historical examination of the colonial history of the community failed to uncover evidence of Historic Trauma as pathology linked to the general process of colonization in the Americas. While evidence emerged of a syndrome linked to attendance at regionally specific Indian residential schools, it was not clear whether this syndrome was distinct from Post Traumatic Stress Disorder. It is suggested that the intergenerational transfer of this symptomatology would involve mechanisms of culture that impact self-construction. Community development is proposed as a method for improving local cultures. The use of psycho-historical analysis is recommended for future research. Abstracto Este artículo examina dos modelos de trauma masivo aplicados a las condiciones sociales e historia de una comunidad indígena en los bosques boreales del norte de Canadá. Este examen de la historia colonial de la comunidad no descubrió evidencia de trauma histórico como patología relacionada al proceso general de colonización de las Américas. Lo que si emergió fue evidencia de un síndrome relacionado con la asistencia a escuelas indígenas residenciales en regiones específicas. No está claro si este síndrome es distinto al trastorno de estrés postraumático. Se sugiere que el traspaso inter-generacional de esta sintomatología incluiría mecanismos culturales que influyen en su autoconstrucción. Desarrollo comunitario se propone como método para mejorar las culturas locales. El uso de análisis psico histórico se recomienda para investigaciones futuras.